STRUGGLE FOR MAINTAINING LOVE OF TOM HANSEN IN MARC WEBB'S 500 DAYS OF SUMMER MOVIE (2009): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - RAMAYANTI, SITI (2011)
The major problem of this study is how struggle for maintaining love is reflected 500 Days of Summer movie based on individual psychological approach. This study analyses structural elements of 500 Days of Summer movie and Tom Hansen's struggle for maintaining his love, based on individual psychological point of view. This research paper is qualitative research. The object study is Tom Hansen as the major character in 500 Days of Summer movie directed by Marc Webb in 2009. The primary data is 500 Days of Summer movie itself and the secondary data are taken from the other data, which have relation with the research, the underlying theory and other materials concerned to the analysis, such as biography of the director, some books of psychology, website about the movie and homepage of the movie. The technique of data analysis is descriptive analysis. the result of the study shows the close relationship between 500 Days of Summer and an individual psychology, particularly in human striving for maintaining his love in 500 Days of Summer movie directed by Marc Webb is about someone's struggle for maintaining his love.